Clustering Approach To Test Case Prioritization Using Code Coverage Metric (International Journal of Engineering and Computer Science, 2014)
Software testing is important phase of software development life cycle which ensures the developer that the developed software works according to specifications or not.  Prioritization techniques that incorporate a clustering approach and utilize code coverage, code complexity and history faults as well to increase the effectiveness of the prioritization. To make testing efficient and effective a techniques of test case prioritization are used. An efficient Test case prioritization technique reduces the cost of testing and fault detection capabilities of testing. Results show that test case prioritization that utilizes a clustering approach can improve the effectiveness of test case prioritization techniques.